Economic growth and foreign direct investment in Asia: When investors imperfectly fulfil approved investment plans - Abigail S. Hornstein (Asia and the Global Economy)
Foreign direct investment (FDI) may represent an expansion in the domestic capital supply, which could thus increase GDP growth through the investment and consumption sectors and generate productivity increases. We examine this hypothesis by looking earlier in the investment process and use little-known data on FDI approvals from ten Asian countries that have routinely required advance approval of FDI and have also disclosed this data. We show that the approved FDI predicts actual FDI inflows, and that on average more FDI is approved than realized. The approved FDI is used to create an FDI commitment ratio and gap, which are thus absolute and relative measures of how FDI pledges are fulfilled. We then examine how the host economy is affected by the FDI commitment ratio and gap using an Arellano-Bond dynamic panel estimator to examine an unbalanced dataset spanning 1967–2022. We find GDP growth forecasts are significantly affected by both FDI measures. However, actual GDP growth is affected negatively by the FDI gap, with the effects strongest at the 3-year horizon. Thus, we show that FDI initially displaces domestic capital before expanding the domestic capital supply.